Augustine's Incarnational Hermeneutics in the "Tractatus in Iohannis evangelium" - Wolter, Sebastian (Teresianum, 2025)
The essay is intended to be a concise summary of central results and insights of the extensive study "Verbum in principio et incarnatum Eine philosophische Einleitung zu Augustins tractatus in iohannis evangelium" by the same author, which was published in Würzburg in 2024 in the Series Cassiciacum. The thesis is: Augustine's metaphysics is his hermeneutics. Augustine's approach is developed from the history of Greek philosophy - more precisely, from the dilemma (between the paradigms of Plato and Aristotle) of a possible metaphysics of the first principle. This neoplatonic problem (mediation of the One) is solved in a certain way by Augustine's philosophy of the incarnation. Access to the knowledge of principles is imparted by the incarnate Word, whose knowledge is in turn imparted in flesh, signs and Holy Scripture, which have to be interpreted. Through the application of the semiotic triangle, Augustine's hermeneutics is analyzed as an incarnational process. Nonetheless, the sign-skeptical consequences of the gracious enlightenment of the inner word (Hadrumentum problem) are discussed. The devaluation of external signs and religion as a sign system ought to be counteracted by the incarnational approach. The remarks conclude with a brief presentation of the spiritual resurrection through spiritual interpretation of Scripture - a doctrine that can also be described as Easter hermeneutics. According to Augustine, spirituality consists precisely in passing over to the spiritual-metaphysical sense of Scripture beyond the visible signs and thus allowing the spirit in God's Word to come alive from the dead letter.